Experiences and Perceptions on Sexuality, Risk and Sti/Hiv Prevention Campaigns by University Students. Designing a Digital Intervention [Experiencias y Percepciones Sobre Sexualidad, Riesgo y Campañas de Prevención de Its/Vih por Estudiantes Universitarios. Diseñando Una Intervención Digital] - Duarte-Anselmi, G; Vanegas-Lopez, J (Associacao Brasileira de Pos - Graduacao em Saude Coletiva, 2022)
This study reports on the qualitative phase of a study that seeks to design a digital intervention for the prevention of STI / HIV and promotion of sexual health in university students. The experience and perception that university students have about sexuality, risk and prevention campaigns are addressed through focus groups. Semi-structured interviews are conducted with key informants. The results reveal that sexual education is limited and restricted to the biological aspect, as well as loaded with prejudices and gender biases, which narrows the information provided to the student population. Wavering prevention strategies that fail to motivate students or offer them opportunities for making informed and independent decisions about their sexual health are apparent. The STI / HIV campaigns assessed are distant, fear-based and not inclusive. Interventions in sexual health do not weigh experiential aspects of youth sexuality, as they are based on models of ideal and stereotyped behavior, discarding first-person narratives and their rich complexity. It is imperative to innovate in the prevention of STI/HIV, formulating interventions based on an integrative, multidisciplinary and contextualized design that values the theory and experience of the target populations. © 2022, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.
Keywords: STI; HIV; Sexuality; Young people; Prevention